Connectivity between the marine coast and estuary for white mullet (Mugil curema) in northeastern Brazil revealed by otolith Sr:Ca ratio. (31st December 2018) - Santana, Francisco M.; Morize, Eric; Labonne, Maylis; Lessa, Rosangela; Clavier, Jacques
Abstract: Microchemical analyses were carried out in order to estimate the Strontium:Calcium (Sr:Ca) ratio in the otolith of the white mullet, Mugil curema, in the Pernambuco (at the Santa Cruz channel, Brazil) in order to determine its connectivity between the estuary and ocean. Variation in the otolith Sr:Ca ratio was directly related to salinity, with greater salinity denoting a higher otolith Sr:Ca value. Data on the otolith Sr:Ca ratio demonstrates that the individuals analyzed are born in areas of salinity that are characteristic of the estuary, where they develop until approximately one year of age, at which point they migrate to areas of greater salinity until reaching sexual maturity (3 years of age) in the sea. Spawning occurs in the ocean, after which M. curema individuals may either remain or return to the estuary until the next spawning. Differences in estuarine salinity were found for young-of-year individuals and may be related to the season when spawning took place, since M. curema females are found spawning throughout the year. The hypothesis is that higher salinity in the dry season leads to a greater otolith Sr:Ca signature among individuals spawned in this season from birth until one year of life. On the other hand, the lower salinity in the rainy season leads to a lower otolith Sr:Ca signature among individuals spawned in this season. These information are important for the adequate management of the white mullet stock in northeastern Brazil.